Formulation Development and Evaluation of Ondansetron Hydrochloride Using Poly Ethylene Glycol 4000 (International Journal of Research in Pharmaceutical Sciences and Technology, 2026)
Ondansetron hydrochloride is a selective 5-HT3 receptor antagonist used to prevent and treat nausea and vomiting caused by chemotherapy, radiotherapy, and surgery. However, its poor aqueous solubility limits dissolution and oral bioavailability. Polyethylene glycol (PEG) 4000 is a solubility enhancer that improves drug dissolution. This study aimed to formulate and evaluate an ondansetron hydrochloride oral solution using PEG 4000 to enhance pharmaceutical performance. Objectives To formulate and develop an oral solution of ondansetron hydrochloride using PEG 4000 as a solubility enhancer, and to evaluate its physicochemical properties, drug content, in vitro drug release, permeability, stability, and potential to improve bioavailability and patient compliance. Methodology The oral solution was prepared using ondansetron hydrochloride and PEG 4000. The formulation was evaluated for appearance, pH, viscosity, and solubility. Drug content and purity were determined using UV spectrophotometry. In vitro egg membrane diffusion studies were conducted to evaluate drug release and permeability. The prepared formulation was also assessed for stability under suitable storage conditions. Results The formulated oral solution showed good clarity, acceptable pH and viscosity, and significantly improved solubility. UV spectrophotometric analysis confirmed satisfactory drug content and purity. The in vitro diffusion study demonstrated enhanced drug release and permeability. The formulation remained physically stable throughout the evaluation period. Conclusion The developed ondansetron hydrochloride oral solution containing PEG 4000 successfully enhanced drug solubility and exhibited satisfactory physicochemical properties, improved in vitro drug release, and good stability. The formulation has the potential to improve bioavailability, therapeutic efficacy, and patient compliance, making it a promising oral dosage form for antiemetic therapy.
Keywords: Ondansetron hydrochloride; 5-HT3 receptor antagonist; PEG 4000